Problems of Atomic Science and Technology 2021
DOI: 10.46813/2021-131-092
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Studies of Pressure and Gap Length Effects on Energy Deposition in Spark Discharge

Abstract: A study of the influence of the discharge gap length and the initial gas pressure on the energy deposition into the discharge channel was done. The study was conducted at the same total discharge energy. It is experimentally shown that the connection of the voltage probe to the discharge circuit significantly affects the discharge current. The determination of the energy deposited into the spark channel is based on the results of numerical simulation of the spark channel development. Experimentally measured di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…According to the results of these studies, a decrease in the critical detonation initiation energy was found with increasing initial gas pressure. In works [5,6], a numerical study of the influence of the initial pressure of inert gas on the development of a spark discharge was carried out, where the influence of pressure on the efficiency of energy input into the spark discharge was revealed. At the same time, studies of processes that occur during spark initiation of detonation under different pressures of a hydrogenoxygen gas mixture were not conducted.…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of these studies, a decrease in the critical detonation initiation energy was found with increasing initial gas pressure. In works [5,6], a numerical study of the influence of the initial pressure of inert gas on the development of a spark discharge was carried out, where the influence of pressure on the efficiency of energy input into the spark discharge was revealed. At the same time, studies of processes that occur during spark initiation of detonation under different pressures of a hydrogenoxygen gas mixture were not conducted.…”
Section: Introductionmentioning
confidence: 99%